Pengaruh Penggunaan Teknik Self Control Dalam Konseling Kelompok Untuk Mengatasi Kecanduan Bermain Game Online Mahasiswa BK Undana - Utami, Fitry; Uda, Geradus; Maria Masi, Lolang; M.A Abel, Rizky (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
The addictive behavior of playing online games experienced by students has a negative impact on students, often students do not attend lectures because the time they spend is only playing online games all day long. The purpose of this study was to find out whether or not there was an effect of using self-control techniques in group counseling to overcome addiction to playing online games.This research uses a quantitative approach with a quasi-experimental type of research (Quasi Experimental), with a research design of One Group Pretest-Posttest. The population of the study was 210 people, the sampling in this study used purposive sampling, namely 7 students with high addiction scores. The collection uses a questionnaire and documentation. Research results: (1) Before participating in group counseling services with self-control techniques, addiction to playing online games is in the very high and high categories with a percentage of 1% and 9%, (2) After participating in group counseling services with self-control techniques, the score for addiction to play is online games decreased in the middle category (3) Students were able to carry out the steps of self-control techniques, (4) t-test values ​​tcount and ttable 12,182> 1,943, meaning that there was a difference in scores between before and after the implementation of group counseling with self-control techniques, (5 ) there is an effect of group counseling with self-control techniques on addiction to playing online games by 73.9%, while some 26.1% are thought to be influenced by other factors.